A Fault in Our Stars: Competitiveness among Michelin-star Restaurants - Miklós, Ilona (Marketing & Menedzsment, 2019)
THE AIMS OF THE PAPER Hospitality is a creative industry. A national cuisine may contribute to a country’s competitiveness by considering the various elements of sustainability in a region, stimulating economical development, and improving the national image. In Europe, the Michelin Star system is the most respected ranking system for high-quality or haute cuisine restaurants. This research is based on whether the characters of Hungarian cuisine can be identified by domestic fine-dining representatives. METHODOLOGY Using qualitative research and content analysis methodology, the paper explores whether fine-dining professionals and Michelin Star restaurants can identify local gastro culinary in the public dialogue. MOST IMPORTANT RESULTS Prizing a Michelin Star could be an innovative or sustainable business strategy, meeting as it does the gastronomic expectations of tourists. Providing a theoretical framework of the relevant literature on the role of innovation within the gastronomy industry, this paper analyses interviews collected from an online media platform. Although not all are covered in this paper, location, co-working, wellbeing and existential balance, inspiration, and burnout are factors identified during the research, factors that could drive Hungarian cuisine in a different direction than others in the international field.